Analisis Determinasi Pemanfaatan Accurate Online dengan Menggunakan Model UTAUT - Silvi Febri Widiyawati; Eko Wahjudi (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2021)
This study aims to examine the factors that influence the behavior of using accurate online in computer accounting subjects based on the acceptance model and use of UTAUT technology. This research is quantitative. The population in this study were 81 students majoring in financial accounting SMK IPIEMS Surabaya institutions, with a research sample of 44 people. Samples were taken based on the purposive sampling technique with the criteria of students who have or are currently taking computer accounting subjects. Data were collected using a questionnaire. The data analysis technique used in this research is the analysis technique of Structural Equation Modeling (SEM). The results show there is a significant positive indirect effect between performance expectancy, effort expectancy and social influence towards the behavior of using accurate online with behavioral intention as a mediating variable.